Investigation of immune responses in different mouse models of allergic asthma - Kirstein, Frank (Department of Clinical Laboratory Sciences, 2023)
Allergies are a common chronic disease and considerably decrease the quality of life for affected individuals. Understanding the immune responses during allergic diseases is essential for both diagnosis and the development of effective therapies. The route of sensitisation to allergens is one factor that influences the immune response and the outcome of allergic diseases and both human and animal studies have highlighted IL-4Ra as an important component in the induction of allergy. The aim of this study was to investigate the contributions of the route of sensitisation to allergens with focus on the significance of cell specific expression of IL-4Ra in the onset of allergy. The route of sensitization to Anisakis pegreffii influences the outcome of experimental allergic asthma: Worldwide, increasing numbers of allergies to the fish parasite Anisakis pegreffii are reported. Anisakis can cause allergies after accidental infection of humans and in the occupational environment. Currently it is not clear if different exposure routes to Anisakis affect the development of allergic asthma and if they have an influence on the immune response. To address these questions, the present study investigated immune responses and disease development after Anisakis live infection and after nasal sensitisation in a mouse model of allergic airway disease. We showed that the route of sensitisation influences the outcome of Anisakis pegreffii induced allergic asthma and demonstrated important contributions of IL-4Ra to the underlying immune response. Alternatively activated macrophages are not necessary for the development of experimental allergic lung inflammation: Development of alternatively activated macrophages (AAM) is induced by signals of IL-4Ra. Alternatively activated macrophages (AAM) are a feature of allergic asthma in clinical and experimental investigations but their role in the development of allergy is not defined. To address this, a model of acute allergic asthma was used to compare mice deficient in AAM (LysMcrelL-4Ra-110x mice) with control mice. We found that the presence of AAM at early stages of allergic airway inflammation these cells was not required for the onset of the disease. Smooth muscle IL-4Ra is not required for experimental allergic asthma: In vitro studies have suggested that IL-4Ra signalling on airway smooth muscle cells (ASMC) is critical for airway irrflammation and airway hyperresponsiveness. Using mice deficient for IL-4Ra in ASMC, the in vivo effects of impaired IL-4Ra signalling in ASMC on the outcome of asthmatic disease were investigated. The impairment of IL-4Ro: on SMC had no effect on major aetiological markers of allergic asthma. These findings suggest that IL-4Ra responsiveness in airway SMC during the acute phase of allergic asthma is not critical for the outcome of the disease. Conclusions: The present study showed the importance of the route of sensitisation and IL4Ra in the development of allergy to Anisakis pegreffii. The use of in vivo models of experimental allergic asthma revealed that the route of sensitisation can influence the underlying immune response of the disease. Furthermore, by using mice with cell specific deficiencies in IL-4Ra it was demonstrated that expression of this receptor on smooth muscle cells and macrophages is not essential for the development of acute experimental allergic airway disease, as it has been previously suggested.